Telepresence-teleguidance to facilitate training and quality assurance in ERCP: a health economic modeling approach - Johanna Brinne Roos; Per Bergenzaun; Kristina Groth; Lars Lundell; Urban Arnelo (Endoscopy International Open, 2020)
Background and study aims The aims of this study was to document the clinical and training relevance of endoscopic retrograde cholangiopancreaticography (ERCP) teleguidance (as a clinical model for applied telemedicine) with health economic modeling methodologies. Methods Probabilities and consequences of complications after ERCP performed by either a novice-trainee or supported through teleguidance (TM) by an expert formed the basis of the health economic model. Results The main clinical and economic outcomes originated from the base case scenario representing a low-volume center. In the cohort the patient age was 62 years, 58 % were females, the expert was doing ≥ 250 ERCPs per year and 50 for the novice-trainee. The expert knowledge transferred was set to 50 % and the average complexity grade to 1.98. Given a willingness to pay threshold of 56,180 USD/ quality-adjusted life years (QALY), the probability of cost-effectiveness of TM assistance was 98.9 %. The probability of a QALY gain for patients having an ERCP, to which was added TM, was 91.6 %. Adding TM saved on an average 111.2 USD (95 % CI 959 to 1021 SEK) per patient, and remained cost-effective basically insensitive to the level of willingness to pay. Conclusion Teleguidance during an ERCP procedure has the potential to be the prefered option in many low- to medium-volume hospitals. The main mechanisms behind these effects are positive impact on several adverse patient outcomes, QALY increase, and decreased costs. TM should be considered for integration into future teaching curriculums in advanced upper gastrointestinal endoscopy.